(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: The Family Adoption Program (FAP) is a vital component of the Competency-Based Medical Education (CBME) curriculum introduced by the National Medical Commission (NMC) of India. The program aims to sensitize medical students to community health needs, enhance communication skills, and develop empathy by fostering direct interactions with families. However, the program also poses distinct challenges for the students. Objective: To find out the perceptions of undergraduate medical students regarding the Family Adoption Program and identify the challenges they face during its implementation. Methodology: A cross-sectional study was conducted among 135 undergraduate medical students in Sree Mookambika Institute of Medical Sciences, who participated in the Family Adoption Program. Data were collected using pretested- questionnaire distributed via Google Forms. After one week again a questionnaire was shared to the students to find out their overall impression regarding the family adoption program based on their reflections. Students who belonged to batches of 2022 and 2023 were included. Feedback on perceptions, communication, and challenges was analyzed. Results: Out of 135, 92.6% knows the Aim and Goals of Family Adoption Program. 79.3% knows the learning domains of Family Adoption Program. 56.3% faces challenges during first visit among that 55.3% is due to difficulty in developing rapport. Students effectively communicated the purpose of their visits to families, with 77% reporting positive cooperation. However, 67.4% identified reluctance on the part of the families to share their health information as a barrier to data collection. Other significant challenges included lack of clinical knowledge and unavailability of family at the time of subsequent visits. Conclusion: Most students acknowledged that the program enhanced their communication skills and understanding of community health issues. Addressing implementation challenges, such as improved clinical skills of students, better community engagement, and revised program timings can further enhance its effectiveness and impact.